2022
DOI: 10.1039/d2lc00177b
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy on-chip: microfluidics for translational radiation oncology

Abstract: The clinical importance of radiotherapy in the treatment of cancer patient justifies the development and use of research tools at the fundamental, pre-clinical, and ultimately clinical levels, to investigate their...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 157 publications
0
5
0
Order By: Relevance
“…The use of specific probiotics and prebiotics to complement CRC treatment has also been studied in clinical trials, showing evidence of their efficacy on the quality of life of patients experiencing fewer symptoms and lowered inflammatory marker concentrations, such as TNF-α levels [101,102]. Clinical trials recapitulated by Shuwen et al showed that SCFAs, from microbial fermentation, have been used as therapeutic treatment against CRC cells [5]. One positive impact is the exertion of a regulatory influence on the immune response by promoting the production of anti-inflammatory cytokines [103] In 2016, Mansouri-Tehrani et al reported the impact of probiotics alone, coupled with honey, and placebo controlled in 67 patients with pelvic cancer receiving radiotherapy, who were exposed to a total dose between 40 and 50 Gy.…”
Section: Using Food Supplements To Mitigate Radiotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…The use of specific probiotics and prebiotics to complement CRC treatment has also been studied in clinical trials, showing evidence of their efficacy on the quality of life of patients experiencing fewer symptoms and lowered inflammatory marker concentrations, such as TNF-α levels [101,102]. Clinical trials recapitulated by Shuwen et al showed that SCFAs, from microbial fermentation, have been used as therapeutic treatment against CRC cells [5]. One positive impact is the exertion of a regulatory influence on the immune response by promoting the production of anti-inflammatory cytokines [103] In 2016, Mansouri-Tehrani et al reported the impact of probiotics alone, coupled with honey, and placebo controlled in 67 patients with pelvic cancer receiving radiotherapy, who were exposed to a total dose between 40 and 50 Gy.…”
Section: Using Food Supplements To Mitigate Radiotoxicitymentioning
confidence: 99%
“…This enables integrated, automated, parallel, and miniaturized biochemical analyses in a consistent manner [115]. It allows representation of in vitro radiotherapy [5], the co-culture of epithelial cells with bacteria [138,139], the modeling of cancer [140,141], drug discovery with toxicity tests [142], and the study of the barrier function [143].…”
Section: Implementing Microfluidic Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…1B), which have recently been reviewed. 13 For example, microfluidic devices uniquely combine radio-compatible materials, culture of increasingly complex tumour models and assay-multiplexing capabilities. The development of chip-based assays could help power translational radiobiology research just as it has positively impacted drug testing for the past 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…These 3D cell cultures often feature key characteristics of in vivo tissues that conventional 2D cell cultures do not offer, making them a relevant biological model. 3D cell cultures embedded in microfluidic devices have been used as a test platform for different chemotherapy, radiotherapy and immunotherapy treatments [15][16][17]. As the plasma medicine community is in the pursuit of accurate and well-established biological models to address key questions of plasma oncology, the use of microfluidic devices could offer solutions from plasma-treated liquid characterization all the way to plasma treatment development.…”
Section: Introductionmentioning
confidence: 99%